EFFECTIVENESS OF TRANEXAMIC ACID IN TRANSURETHRAL RESECTION OF THE PROSTATE (TURP) PROCEDURE ON BENIGN PROSTATE HYPERPLASIA (BPH): A SYSTEMATIC REVIEW AND META-ANALYSIS - Manalu, Yustika Veronica; Warli, Syah Mirsya; Kadar, Dhirajaya Dharma; Amelia, Sri (Indonesian Journal of Urology, 2022)
Objective: This study aims to determine the effectiveness of tranexamic acid in the TURP procedure in BPH patients. Material & Methods: This meta-analysis research was performed online literature from Pubmed, Google Scholar, Cochrane, and Science Direct with a data collection period from July 2020 to October 2020. The journals used are journals regarding all studies on the effectiveness of tranexamic acid in the TURP procedure on BPH with criteria inclusion were BPH patients receiving TURP-invasive therapy and receiving tranexamic acid before or after surgery vs. no intervention or placebo. The results assessed were in terms of the amount of bleeding, volume of irrigation fluid, duration of operation, and weight of the resected prostate tissue. The statistical analysis was performed in Review Manager v.5.4. Results: We found 6 studies that fitted into our criteria with 436 patients were identified. We found a significant difference of decreasing blood loss between tranexamic acid and control that tranexamic acid was more effective than control (MD -125.39, 95% CI: -247.21 - 3.36, P = 0.04). There was no significant difference of the amount of Hb (MD 0.06, 95%, CI: -0.17 – 0.28, P = 0.63). There was also no significant differences of volume irrigation fluid (MD 0.79, 95%, CI: -1.18 – 2.76, P=0.43), duration of operation (MD 14.55, 95%, CI: -32.56 – 3.47, P = 0.11) and weight of resected prostate tissue (MD 0.77, 95% CI: -1.06 – 2.6, P=0.77). Conclusion: Tranexamic acid is effective in decreasing blood loss in the TURP procedure.